Role of ethnicity/language in documented rates of pediatric asthma prescription refills. (1st February 2023) - Lucas, Jennifer A.; Kaufmann, Jorge; Jones, Matthew; Garg, Arvin; Ezekiel-Herrera, David; Puro, Jon; Marino, Miguel; Heintzman, John
Abstract: Objective: Medication maintenance is critical in the management of asthma. We investigated the differences in electronic health record (EHR) documentation of medication refills for Spanish- and English-speaking Latino children and non-Hispanic white children by examining rates of albuterol rescue inhaler refills from 2005 to 2017, and and inhaled corticosteroid refills from 2015 to 2017 in a multi-state network of community health centers (CHCs). Methods: We used data from the ADVANCE network of CHCs. Our sample consisted of children aged 3–17, with a diagnosis of asthma and either albuterol or inhaled corticosteroid prescriptions ( n  = 39, 162; n  = 4, 738 children, respectively). Negative binomial regression was used to calculate rates of refills per prescription adjusted for relevant patient-level covariates. Analyses stratified by asthma severity were also conducted. Results: English-speaking Latino children had lower rates of albuterol refills compared with non-Hispanic white children (rate ratio [RR] = 0.88, 95% confidence interval [CI]: 0.80–0.98), a trend that persisted among children with moderate/severe persistent asthma severity (RR = 0.85, 95% CI: 0.76–0.95). Spanish-speaking Latino and non-Hispanic white children had similar albuterol refills. Inhaled corticosteroid refill rates were comparable between all groups. Conclusions: In a multi-state network, these findings suggest that CHCs deliver equitable asthma care related to prescription refills between their Latino and white patients, but there is still opportunity for providers to ensure that their English-speaking Latino patients have access to necessary emergency asthma medication.